Impulsive control of single-input nonlinear systems with application to HIV dynamics - Rivadeneira Paz, Pablo Santiago (2012)
In this paper, some fundamental analysis and results are introduced for the accessibility of impulsive control systems (ICS). The main result is the characterization of accessibility for nonlinear ICS based on the `number of impulses´ which is required. These results naturally generalize and correct some earlier results obtained for linear ICS. The theory developed is applied to an impulsive model of the dynamics of human immunodeficiency virus (HIV) subject to medication. It is shown that HIV system fulfills the accessibility criterion. Finally, an impulsive control strategy is designed based on exact linearization to improve the response inmune system of a patient of HIV.